Pengaruh Asupan Protein dan Zat Besi (Fe) terhadap Kadar Hemoglobin pada Wanita Bekerja - Agus Hendra Al Rahmad (Jurnal Kesehatan, 2017)
Anemia is a condition where the hemoglobin (Hb) is lower than the normal value according to age and sex of a person caused by certain factors, including intake of nutrients one protein and iron, with the percentage of women in Indonesia who have anemia amounted to 23,9%. The high prevalence is thought to be associated with low intake of protein and iron in women. This study aimed to measure the effect of protein intake and iron (Fe) to the hemoglobin in women working. This analytical study used cross-sectional design with 69 samples of working women conducted in Panteraja Sub-district Pidie Jaya District, in November-December 2016. Research variable that is protein and iron intake was measured used 24-hour recall in 2 days, and hemoglobin level was examined by easy touch. Data analysis is univariate and bivariate using Pearson correlation test. The results showed a significant influence of protein intake (p=0,000 and r=0,7) and iron intake (p=0,000 and r=0,6) on Hb levels in women working in Panteraja District with strong and patterned strength positive. It can be concluded that the intake of protein and iron has a strong effect on the increase of Hb level, that is the increase of protein and iron intake Hb level in woman work increasingly.